Analisis Literatur: Strategi Pembelajaran Inovatif untuk Meningkatkan Motivasi Belajar Siswa - Santika, Atik; Eliawati, Neni; Sopiah, Ai Durotus (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Innovative learning strategies refer to approaches that encourage students to internalize subject matter through the use of a variety of engaging and interactive methods and media. Students' learning motivation has a very important role and cannot be ignored, because this motivation directly affects their learning outcomes. This journal aims to explore various innovative learning strategies that can increase students' motivation to learn. In the writing process, the author uses a literature study method by collecting data and sources relevant to the research topic. The result of this writing is an analysis of innovative learning strategies that have the potential to increase student learning motivation.This study emphasizes the importance of learning motivation in influencing students' academic outcomes, and shows that innovative methods such as flipped learning, blended learning, and e-learning can contribute to improving the quality of education.